What’s in the Pipeline? Evidence on the Transmission of SARS-CoV-2 via Building Wastewater Plumbing Systems - Dight, Thomas; Gormley, Michael (Frontiers in Built Environment, 2021)
There is growing evidence of the transmission of SARS-CoV-2 via the sanitary plumbing wastewater system, a known transmission pathway of SARS-CoV-1. Such occurrences can no longer be dismissed as isolated cases, yet a lack of awareness and of basic research makes it impossible to say just how widespread this mode of transmission might be. Virus is transmitted within wastewater systems by the aerosolisation of wastewater and subsequent transport of bioaerosols on naturally occurring airflows within the piped network. Central to the debate around risk to building occupants from SARS-CoV-2 spread via wastewater plumbing systems is the question of infectivity of faeces, urine and associated aerosols. This paper presents an examination of the processes which underlie this mode of transmission, and the existing epidemiological evidence, as well as existing mitigation strategies; significant gaps in the state of the knowledge are also identified. In writing it, we hope to facilitate the selection and adoption of appropriate mitigation strategies, and to highlight key avenues for future research spanning the underlying science, the collation of further epidemiological data, and the development of the strategies and standards necessary to protect people from this most overlooked of threats.